Correlation between pulmonary to systemic flow ratio and N-terminal Pro-B-type natriuretic peptide level in children with atrial septal defect - Liao, Li-Chin; Chen, Yun-Yu; Fu, Yun-Ching; Hung, Hui-Chih (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtrial septal defect (ASD) increases pulmonary to systemic flow ratio (Qp/Qs) which is an important determinant factor for treatment. N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels are correlated with volume overloading of the heart. This study aims to explore the relationship between Qp/Qs and NT-proBNP levels in children with ASD.Materials and methodsBetween January 2010 and December 2023, 464 patients under 20 years old with ASD who underwent cardiac catheterization and received NT-proBNP test were enrolled retrospectively. Baseline characteristics such as sex, body weight, and age were recorded. Qp/Qs was measured during standardized right heart catheterization according to Fick principle.ResultsA significant positive correlation existed between NT-proBNP and Qp/Qs (R = 0.507, P < 0.001), with an R2 of 0.258. The linear regression model indicates that a one-unit (pg/ml) increase in NT-proBNP corresponded to a 0.003-unit increase in Qp/Qs (P < 0.001). Patients with a Qp/Qs ratio ≥ 2 had significantly higher NT-proBNP levels than those with a ratio <2 (P < 0.001).ConclustionThis study, the largest cohort to date, reveals the correlation between non-invasive NT-proBNP level and invasive Qp/Qs measurement in children with ASD.